Control BLDC Motor Speed using PID Controller - Mahmud, Md; Motakabber, S. M. A.; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (Science and Information Organization, 2020)
At present, green technology is a major concern in every country around the world and electricity is a clean energy which encourages the acquisition of this technology. The main applications of electricity are made through the use of electric motors. Electric power is converted to mechanical energy using a motor, that is to say, the major applications of electrical energy are accomplished through electric motors. Brushless direct current (BLDC) motors have become very attractive in many applications due to its low maintenance costs and compact structure. The BLDC motors can be substituted to make the industries more dynamic. To get better performance BLDC motor requires control drive facilitating to control its speed and torque. This paper describes the design of the BLDC motor control system using in using MATLAB/SIMULINK software for Proportional Integral Derivative (PID) algorithm that can more effectively improve the speed control of these types of motors. The purpose of the paper is to provide an overview about the functionality and design of the PID controller. Finally, the study undergoes some well-functioning tests that will support that the PID regulator is far more applicable, better operational, and effective in achieving satisfactory control performance compared to other controllers.